2016
DOI: 10.1124/mol.116.105882
|View full text |Cite
|
Sign up to set email alerts
|

Differential Inhibition of Water and Ion Channel Activities of Mammalian Aquaporin-1 by Two Structurally Related Bacopaside Compounds Derived from the Medicinal PlantBacopa monnieri

Abstract: Aquaporin-1 (AQP1) is a major intrinsic protein that facilitates flux of water and other small solutes across cell membranes. In addition to its function as a water channel in maintaining fluid homeostasis, AQP1 also acts as a nonselective cation channel gated by cGMP, a property shown previously to facilitate rapid cell migration in a AQP1-expressing colon cancer cell line. Here we report two new modulators of AQP1 channels, bacopaside I and bacopaside II, isolated from the medicinal plant Bacopa monnieri Scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 55 publications
6
66
0
Order By: Relevance
“…However, to date few AQP inhibitors have been discovered as suitable candidates for clinical development. Currently, the sulfhydryl‐reactive, heavy metal‐containing compounds and some compounds isolated from medicinal plant have been confirmed as AQP1 inhibitors; however, there is still a need to identify useful inhibitors with therapeutic application in the clinic and limited side effects . In our study, we found a new agent from natural products that can inhibit the expression of AQP1 in a dose‐dependent and time‐dependent manner and improve barrier dysfunction.…”
Section: Discussionmentioning
confidence: 75%
“…However, to date few AQP inhibitors have been discovered as suitable candidates for clinical development. Currently, the sulfhydryl‐reactive, heavy metal‐containing compounds and some compounds isolated from medicinal plant have been confirmed as AQP1 inhibitors; however, there is still a need to identify useful inhibitors with therapeutic application in the clinic and limited side effects . In our study, we found a new agent from natural products that can inhibit the expression of AQP1 in a dose‐dependent and time‐dependent manner and improve barrier dysfunction.…”
Section: Discussionmentioning
confidence: 75%
“…Block by AqB011 of the AQP1 ionic conductance demonstrated that the cation channel activity is a key component for HT29 cancer cell migration Figure . The continuing evaluation of traditional medicinal plants as sources of blockers of AQP1 has produced agents that selectively inhibit water permeability (such as bacopaside II), or that block both the water and ion channel pores (such as bacopaside I); these also are promising tools for controlling migration in the subset of cancers that rely on AQP1 expression . Bacopaside II isolated from the traditional medicinal herb Bacopa monnieri blocks the migration of cancer cells measured in live‐cell‐imaging assays (Figure ) without toxicity at effective doses …”
Section: Future Directionsmentioning
confidence: 99%
“…Highlighted in blue is the loop D domain, in red are the double arginine residues at positions 159 and 160 (R159 + R160) located in the loop D domain. The double arginine site is proposed to be involved in binding of the agonist cGMP and antagonists AqB011 and bacopaside I . Cysteine at position 189 (cyan) is the mercury binding site .…”
Section: Introductionmentioning
confidence: 99%
“…The role of ion channels in vascular alteration occurring in the metastatic process is clearly recognized but still not completely elucidated, as discussed by Klumpp, L. et al Therefore, we believe that all these ion channels reported by Klumpp, L. et al [1]. , us [2] and others [3,4,5,6,7,8,9] may have a mechanistic role in the primary tumor set up as well as in the metastatic progression toward the brain and other organs.…”
Section: To the Editormentioning
confidence: 89%
“…For instance, we [2] evaluated the expression of ninety ion-channel genes in 3673 human biopsies, in five different solid tumors (bladder cancer, breast cancer, glioblastoma, lung cancer and melanoma). We [2] and others [3,4,5,6,7,8,9] have shown a key role of ion channels in tumors common to Klumpp, L. et al, namely lung cancer, breast cancer and melanoma, as well as in other cancers such as glioblastoma, bladder cancer and colorectal cancer. These channels are calcium channel voltage-dependent (CACNA1D); FXYD domain-containing ion transport regulators (FXYD3, FXYD5); chloride intracellular channels (CLIC1); glutamate receptors (HTR3A); potassium channel voltage-gated channels (KCNE3, KCNE4, KCNN4); transient receptor potential cation channels (TRPA1, TRPC5, TRPM3, TRPV4) and Aquaporins (AQPs).…”
Section: To the Editormentioning
confidence: 99%